Advanced Pediatric Emergency Airway Management: A Multimodality Curriculum Addressing a Rare but Critical Procedure - Michael P. Goldman; Ambika Bhatnagar; Joshua Nagler; Marc A. Auerbach (Association of American Medical Colleges, 2020)
Introduction Advanced airway management in pediatrics is a rare, high stakes skillset. Developing proficiency in these skills is paramount, albeit challenging. Providers require innovative approaches to address initial training and maintenance of procedural competency. To address this, we developed a multimodality curriculum. Methods Through an interactive problem-based learning session utilizing real intubation videos, hands-on skill stations, and two simulation-based scenarios, participants advanced through educational objectives towards the goal of improving perceived comfort, knowledge, skills, and attitudes in emergency pediatric advanced airway management. Content was developed by integrating varied learning modalities under the learn, see, practice, prove, do, maintain construct. Please note the specialized equipment needed for this curriculum included pediatric airway trainers and a video laryngoscope. Results We have conducted the curriculum in its entirety four times, reaching 131 interdisciplinary participants. Forty-nine physicians of varying training backgrounds and clinical working environments completed postparticipation evaluations. On a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree), a significant improvement in perception of comfort with managing the emergent pediatric airway was noted (2.7 to 4.6, p < .0001). Further, 94% of participants reported they strongly agreed (71%) or agreed (23%) that each station added to their perceived knowledge, skills, and attitudes of pediatric airway management. Discussion After participating in our curriculum, participants self-reported improved comfort in managing the emergent pediatric airway. This curriculum provides educators with resources to navigate the paradigm of obtaining and maintaining competency of a rare but critical skillset.